Comparison of phase equilibria between FactSage predictions and experimental results in titanium oxide-containing system. (December 2018) - Wang, Shuai; Chen, Mao; Guo, Yufeng; Jiang, Tao; Zhao, Baojun
Abstract: In the present study, FactSage predictions were systematically compared from the present experimental results and the experimental data from the literatures in the CaO-SiO2 -MgO-Al2 O3 -"TiO2 " system. These results reveal that the discrepancies are significant between the predictions and experimental results. The predicted primary phases in CaTiO3 and TiO2 primary phase fields were consistent with the experimental results, but a number of inconsistent results were found in other primary phase fields including M3 O5 and spinel. The predicted liquidus temperatures were higher than the experimentally determined liquidus temperatures at low titanium level (< 20 wt% TiO2 ), whereas the predicted liquidus temperatures were much lower than the experimentally determined liquidus temperatures at high titanium section (> 40 wt% TiO2 ). In TiO2 primary phase field, the experimentally determined liquidus temperatures can be 130 °C higher than the predicted ones. Up to 107 °C differences still exist between the experimental results and predictions for the liquidus temperatures in M3 O5 primary phase field. The Al2 TiO5 phase has a significant influence on the phase equilibria in the M3 O5 primary phase field but it is not included in the current FactSage database.